EFEKTIVITAS EKSTRAK BUNGA KAMBOJA PUTIH (Plumeria alba. L) SEBAGAI DENTURE CLEANSER TERHADAP PERTUMBUHAN Candida albicans PADA BAHAN BASIS GIGI TIRUAN NILON TERMOPLASTIK (Valplast) Effectiveness Of Cambodia White Flower Extract (Plumeria alba L.) As Dent - Fitriana Wadianur; Lusi Hidayati; Yani Corvianindya Rahayu (Pustaka Kesehatan, 2018)
Background: Nylon thermoplastic (Valplast) is a flexible denture base that is used in the denture. The problem that often occurs in the use of denture namely the denture stomatitis are commonly caused by C. albicans. Denture cleanser is needed to prevent denture stomatitis by lowering the amount of C. albicans. Recently, denture cleanser from natural materials is being develope, one of them is cambodia white flower (Plumeria alba L.) extract. Cambodia white flower (Plumeria alba L.) contains bioactive compounds that are antibacterial and antifungal. Objective: To determine the effectiveness of immersion extract of cambodia white flower (Plumeria alba L.) with various concentrations as denture cleanser to amount of C. albicans in nylon thermoplastic (Valplast). Material and Methods: 25 plates nylon thermoplastic (10x10x1mm) were prepared and divided into 5 groups. The plates then contaminated with C. albicans, after that it was soaked in cambodia white flower extracts with varying concentrations for 30 minutes. The plates are subsequently placed in SDB media. Method to test the effectiveness of extract was done by looking at the SDB media turbidity with a spectrophotometer. Results and Conclusion: Cambodia white flower extract was effective in lowering the amount of C. albicans in denture base thermoplastic nylon. Cambodia white flower contained tannin, flavonoid, alkaloid and saponin which acted as antifungal that could decrease the amount of C. albicans. Keywords: Antifungal, Candida albicans, Nylon Thermoplastic and Cambodia White Flower